Integrasi Pendidikan Islam Moderat Dengan Pendekatan Inklusif: Studi Kasus di SMP Negeri 21 Surabaya - Chalimatus Saadah; Maftuh, Maftuh (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the integration of moderate Islamic education with an inclusive approach in the formal educational setting of SMP Negeri 21 Surabaya. The research is grounded in the importance of shaping a tolerant and open-minded generation capable of living harmoniously in a multicultural society through a balanced and adaptive Islamic religious education. The study employed a descriptive qualitative method with a case study approach. Data were collected through observations, in-depth interviews with Islamic Education (PAI) teachers and the school principal, as well as documentation of learning activities. The findings reveal that the integration of moderate Islamic values is reflected in the learning materials, teaching methods, and student activities such as social service, Dhuha prayer, and daily sermons. The inclusive approach is implemented by instilling interfaith tolerance, recognizing diversity, and fostering a learning atmosphere that respects differences. Teachers play a crucial role in internalizing moderation values through exemplary conduct and diversity-friendly pedagogical methods. This integration not only enhances students' understanding of peaceful and rahmatan lil ‘alamin Islamic teachings but also strengthens their social character. This study contributes conceptually and practically to the development of a more moderate and inclusive Islamic Education curriculum. In conclusion, an inclusive approach to moderate Islamic education in public schools can create a humanistic, tolerant, and inclusive learning environment, relevant to the diverse context of Indonesian society today